COMPARATIVE STUDIES ON PHYSICOCHEMICAL PROPERTIES OF MORINDA CITRIFOLIA GEL AND OINTMENT FORMULATIONS - PATAWEEKORN KETKOMOL; TADSANEE PUNJANON (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study is comparing the physicochemical properties of Morinda citrifolia formulation in various conditions. Methods: Methanolic fruit extracts of M. citrifolia were used for the preparation of gel and ointment formulations that were evaluated for their phytochemicals, physicochemical, and stability at various conditions. Results: Phytochemical screening studies of M. citrifolia revealed the presence of bioactive. Furthermore, the evaluation of physical and chemical stability showed that gel formulation was more stable than ointment formulation. Conclusion: Gel formulation could become a media to be used for its medicinal properties.